Animal drugs and the milk supply - Wilson, R.W. (Kansas Agricultural Experiment Station, 2012)
The makers of the laws, rules, and regulations governing the production and processing of milk have recognized that milk is the primary diet of the very young and old. This fact mandates that it should be produced and processed in a manner to protect and maintain it in a pure, safe, and unadulterated condition. To determine adulteration of any milk product, one must first understand the legal definition of that product. In general, milk is defined as "the lacteal secretion of healthy cows that is practically free from colostrum." Anything that alters the product from the intent of this definition constitutes adulteration.
Keywords: Dairy; Animal drugs; Milk supply